Molecular engineering of terpyridine-Fe(II) coordination polymers consisting of quinoxaline-based π-spacers toward enhanced electrochromic performance. (21st September 2022) - Shu, Min; Tao, Jiayu; Han, Yiying; Fu, Wenan; Li, Xiaowei; Zhang, Rui; Liu, Jian
Abstract: In this work, four new terpyridine-Fe (Ⅱ) coordination polymers (FeQ1 ∼ FeQ4 ) consisting of quinoxaline-based π-spacers were developed, and further deposited on ITO substrates via spin-coating process for electrochromic applications. All these Fe (Ⅱ) coordination polymers exhibited fast and reversible electrochromic switching between purple and yellow with high optical contrast as well as high coloration efficiency, and showed good cycle stability. The variation of substituents on the quinoxaline-based π-spacers resulted in tunable electrochromic properties. Remarkably, polymers FeQ3 and FeQ4 with aliphatic substituents on the ligands showed superior optical contrast up to 76.7% and 81.6% around 575 nm, with coloring time around 0.5 s and bleaching time around 2 s, respectively. To the best of our knowledge, FeQ4 gained the highest optical contrast value among the reported electrochromic materials based on Fe-complexes up to date. Graphical abstract: We developed four terpyridine-Fe(II) coordination polymers consisting of quinoxaline-based π-spacers for electrochromism with enhanced performance. Image 1 Highlights: Four new Fe(II) coordination polymers were prepared for electrochromics. Quinoxaline-based π-spacers were introduced for enhanced electrochromic performance. FeQ4 showed fast purple-to-yellow switching with high optical contrast over 80%.